What Is Going On? An Analysis of the Interaction Order - Halldorsson, Vidar (Qualitative Sociology Review, 2022)
Seeing sociology visually adds a sense of realness to the viewer compared to only reading sociological texts. In this paper, I aim to provide an example of how a single scene from a feature film can be utilized as a practical and meaningful means to analyze a social situation and to help students of sociology to grasp key features of Goffman’s theory of interaction order. More precisely, the main aims of the paper are 1) to illustrate Goffman’s theory of the interaction order by identifying acts of disruption and alignment in interaction through a film clip; and 2) to attempt to analyze, in a Goffmanian sense, what is really going on in the situational interaction. The scene is from the 2013 American movie August: Osage County and follows a dinner of immediate family in the wake of the funeral of the hostess’s late husband. The normative and civilized interaction of the meal is, however, jeopardized by the hostile and provocative mood of the hostess, as she repeatedly disrupts the interaction order with attempts to mock and/or uncover the hidden and vulnerable truths of the immediate members of her family, exemplifying her power status in the particular situation. The dinner guests, however, try to overlook and resist the provocation of the hostess and stick to their predetermined roles to save and sustain their idealized selves (their faces) and the interaction order (the faces of others), In doing so they, on the one hand, discard the uncomfortable truths acclaimed by the hostess and, on the other, explain the hostess’s provocative actions in terms of their claim that she is unwell and in need of medical attention. Thus, the attacked dinner guests in the scene align more alliance to the interaction order than to truth itself.